Male Make-up Artist Self-concept Against Social Bullying - Cosmas Gatot Haryono; Meysca Meysca (Warta Ikatan Sarjana Komunikasi Indonesia, 2022)
This study looks at the self-concept of men who work as make-up artists in Jakarta. The majority of Indonesians who still follow a patriarchal culture believe that the make-up artist profession should be performed by women because the world of make-up, make-up, and beauty are the hallmarks of femininity. As a result, a man who works as a make-up artist still invites the public's pros and cons to this day. The constructivist paradigm is used in this study, along with qualitative research methods and Alfred Schutz's phenomenological theory. Researchers used observation and interview techniques, such as semi-structured interviews and in-depth interviews, to collect data for this study.According to the study's findings, not all men who work as make-up artists adopt or apply all of the characteristics of women. The study's resource persons were able to distinguish between the context of their soul and the context of their body, allowing them to limit and assume that the make-up artist profession is only a passion and a promising job opportunity.